Strategi Kepala Desa Ekas Buana dalam Pengembangan Infrastruktur Pariwisata Berbasis Masyarakat di Desa Ekas Buana - Tio Pramana Aribawa; Usman; Kamaruddin (Pendidikan Al-Gafari, 2024)
The tourism sector is strategic in donating income areas as well as increasing the economy public. Income from activity tourism also contributes to the absorption power of Work. Study This aims To know What is the Strategy of the Head of Ekas Buana Village in Development. Infrastructure Tourist Community-Based. As for types of study, This is qualitative purposeful descriptive To explain or describe something circumstances, events, objects like people, or something related to the study. Analysis of the data obtained based on data in the field, in the analysis process, own four stages that are reduction, triangulation, data presentation, verification/conclusion. Based on research conducted through interviews, observations, and documentation. Research results show that the head village has carried out a strategy that can be seen from three draft basics, that is matter Power attraction, accessibility, and amenities, ie as follows. (1) Create/improve service information easily and fast tourism access travelers through print and online media as well as increase quality infrastructure and facilities transportation going to location object tour. (2) Interweave cooperation with Local Government and parties private sector for the development of infrastructure more directed, integrated, and effective that fulfills standard appropriateness infrastructure tourists especially problem provision of clean water, transportation, and lighting roads. (3) Improve quality cleanliness and add public toilet facilities for comfort tourists use guard beauty and health on-site environment object tour. (4) Planning and creating system disposal rubbish on site object tour to create a sense of comfort for travelers and increase role as well as/involvement public to activity maintenance and maintenance infrastructure and facilities tour.